Fabrication of Silver Nanostructures in the Form of Particles, Dendrites and Flowers on Silicon for Use in SERS Substrates - Dao Tran, Cao; Luong Truc Quynh, Ngan; Cao, Tuan Anh; Kieu Ngoc, Minh (Communications in Physics, 2022)
Surface Enhanced Raman Scattering (SERS) is a technique that is increasingly being used to detect trace amounts of various types of molecules, especially organic and biological molecules. The SERS effect is available mainly due to the SERS substrate - a noble metal surface that is rough at the nano level or a set of noble metal nanoparticles in a certain arrangement. Such a SERS substrate acts as an analyte Raman signal amplifier and can provide amplification up to millions of times and even more. The amplification coefficient of the SERS substrate is determined mainly by the number of ‘hot spots’ it contains as well as the ‘hotness’ of these spots. In turn, a ‘hot spot’ is a certain space around the tips or a nanogap between particles, where the local electromagnetic field is intensely enhanced, while the ‘hotness’ is determined by the sharpness of the tips (the sharper the hotter) and tightness of the gaps (the narrower the hotter). This report presents an overview of the research results of fabricating a type of SERS substrate with a high enhancement factor, which is the SERS substrate made from silver nanostructures coated on the silicon surface. With the aim of increasing the number of ‘hot spots’ and their quality, as well as ensuring uniformity and reproducibility of the SERS substrate, silver nanostructures have been fabricated in various forms, such as nanoparticles, nanodendrites and nanoflowers. In addition, the report also mentions the use of the above silver nanostructures as SERS substrates to detect trace amounts of some pesticides and other toxic agents such as paraquat, pyridaben, thiram, cyanide...